Advancing workforce competency: Singapore’s integration of competency-based education (Journal of Applied Learning and Teaching, 2024)
This opinion piece investigates the evolution of Singapore’s education system through the integration of Competency-Based Education (CBE), driven by global economic changes and the country’s vision for a future-ready workforce. It explores how CBE’s focus on mastery over rote learning prepares learners for real-world challenges, fostering critical thinking and adaptability. Anchored by policies like SkillsFuture and collaboration with industry, this article examines Singapore’s commitment to lifelong learning and skill mastery, enhancing employability and resilience among Singaporeans. The discussion contributes to educational reform, highlighting Singapore’s innovative model that aims to equip learners with the competencies needed to thrive in the 21st century. By analysing current trends, implementation strategies, and potential challenges, it provides a comprehensive overview of CBE’s impact on higher education in Singapore, offering insights and recommendations for future developments.